Food town, USA : seven unlikely cities that are changing the way we eat - Winne, Mark, 1950- (Island Press, 2019)
"Mark Winnes Food Town, USA is a tasty, heartwarming journey through towns wed never thought much of but suddenly want to move to. It happily reminds us that when we devote ourselves to people and places we care about, wonderful and unexpected things seem to happen." Mark Bittman, author of the How to Cook Everything series, Food Matters, and VB6: Eat Vegan Before "Food Town, USA may prove to be the most hopeful and important book to take the food movement out of the predictable culture wars between big city and forgotten countryside, between blue and red, and between glamorous and unfashionable places. Whether its craft beer or food sovereignty, Winne gives voice to those who are reinventing the food movement in their own language." Richard McCarthy, Executive Committee, Slow Food International "As only a longtime leader in the food movement can, Mark Winne introduces us to the unsung heroes of local food revitalization, demonstrating how food policy councils, farmers' markets, community gardens, and farm-to-school programs can help struggling communities rebuild." Liz Carlisle, author of Lentil Underground and coauthor of Grain by Grain